Distinct Factors Secreted by Adipose Stromal Cells Protect the Endothelium From Barrier Dysfunction and Apoptosis - Lu, Hongyan; Merfeld-Clauss, Stephanie; Jawed, Yameena; March, Keith L.; Coleman, Michael E.; Bogatcheva, Natalia V. (Frontiers in Cell and Developmental Biology, 2020)
We had shown previously that adipose stromal cell (ASC)-derived conditioned media (CM) limited lung injury, endothelial barrier dysfunction and apoptosis. Here, we used endothelial hyperpermeability and apoptosis assays to investigate how concentration processes affect endothelium-directed bioactivity of ASC-CM, and gain information on the nature of bioactive factors. Comparison of ASC-CM concentrated with differential MW cut-off filters showed that endothelial barrier protection depended on the species-specific factors in ASC-CM fractionated with MW >50kDa. Known barrier regulators KGF, VEGF, and HGF were detected in ASC-CM fraction of >100kDa. Pretreatment of endothelial monolayers with concentrations of KGF, VEGF, and HGF detected in ASC-CM showed that only KGF and HGF protect endothelium from barrier dysfunction. Depletion of KGF and HGF from ASC-CM attenuated ASC-CM ability to protect endothelial barrier. In contrast to barrier-protective factors, apoptosis-protective factors fractionated with MW <3kDa and were not species-specific. Application of donors of apoptosis-mitigating gases showed that CO donor CORM2 protected endothelium from apoptosis, while H2S donor NaSH did not. Knock-down of CO-generating heme oxygenase 1 in ASC attenuated ASC-CM ability to protect endothelium from apoptosis. We have shown that TNFα-induced apoptosis in endothelium is JNK-dependent, and JNK activation is inhibited by ASC-CM pretreatment of endothelial cells. ASC-CM from heme oxygenase 1-depleted ASC displayed attenuated ability to suppress endothelial JNK activation, suggesting that CO-mediated protection of endothelium from apoptosis is achieved by the downregulation of JNK pathway. Altogether, our results demonstrate that concentration of ASC-CM with low MW cut-off filters significantly reduces its anti-apoptotic activity while preserving barrier-protective activity.